Book Review: Palestine: A Four Thousand Year History by Nur Masalha - Alaqad, Mohammed H. (The International Journal of Palestine Studies, 2025)
In Palestine: A Four Thousand Year History, historian Nur Masalha challenges the colonial narrative that views Palestine as a modern invention. Drawing on archaeology, cartography, and historical texts, he traces the continuous presence and identity of the Palestinian people over millennia. From ancient Philistia to the Arab province of Jund Filastin and beyond, Masalha highlights local agency and the region’s pluralistic heritage, including the contributions of Arab Christians and Muslims. He critiques Zionist historiography, biblical archaeology, and the erasure of indigenous place names, framing these as tools of settler-colonialism. This decolonial history restores dignity to Palestinian identity and resists historical erasure. A companion website with digital resources could further amplify its impact. As a Palestinian scholar, I see this book as both a scholarly achievement and a powerful act of resistance.